(untitled) (Nigerian Journal of Physiological Sciences, 2023)
Anaemia is a widespread health issue affecting young children and pregnant women, characterized by reduced red blood cells or haemoglobin levels. Coconut water, rich in nutrients such as L-arginine, iron, vitamin C, vitamin B6, folic acid and fatty acids, is believed to aid in blood formation (hematopoesis). The study aimed to examine the impact of coconut water on hematological indices and lipid profiles in rats with phenylhydrazine-induced anemia. 30 rats were divided into 5 groups: a normal control, phenylhydrazine untreated, coconut water (0.5ml/kg), iron, and ferrous treated groups. Hemoglobin, hematocrit, and erythrocyte levels were measured using a Hematology Analyzer. Results showed a significant decrease in LDL and TG levels, and an increase in HDL levels in phenylhydrazine induced anemia compared to the control group. Coconut water administration at 0.5ml/kg reduced LDL, VLDL and TG levels, and increased HDL levels in rats with induced anemia. The study found that coconut water had a positive effect on hematological indices, as it increased hemoglobin and erythrocyte levels in rats with induced anemia. These findings suggest that coconut water may have potential therapeutic benefits for individuals with anemia, particularly in lowering lipid levels and improving blood formation. However, further research is needed to fully understand the mechanisms underlying these effects and to determine the most effective dosage and duration of treatment. Overall, the study highlights the importance of coconut water as a potentially beneficial alternative treatment for anemia.